Peranan Pelatih Dalam Memotivasi Pemain Sepakbola: coach, motivation - Cholid, Abdul (Fakultas Pedagogi dan Psikologi Universitas PGRI Adi Buana Surabaya, 2015)
Football is one of the most popular sport in Indonesia and the world When the development isn It succeeded, the coaches' role would be reviewed as the responsibility is consideredto be found in them. When a match is succeded and meet their fans expectation, the coach would be praised. Otherwise, when a match isn't succeeded, the coach would be blamed. Therefore a coach needs to be able to motivate the players, because the players could be driven to win. To motivate, the coach needs to have a good mental state and good performance. With a good attitude and mental, the coach can be a good modelfor the players. Mental readiness and endurancce is very important to motivate the players. A coach needs to evaluate player's mental state so they keep improving.